Demystifying the nutritional and anti-nutritional genetic divergence of Pakistani chickpea (Cicer arietinum L.) genetic resource via multivariate approaches - Jameel, Saima; Hameed, Amjad; Shah, Tariq Mahmud; Coyne, Clarice J. (Frontiers in Nutrition, 2024)
Chickpeas are a highly versatile functional food legume that possesses the capacity to boost human health and has the potential to alleviate malnutrition-related deficiencies. To investigate whole seed-based nutritional and anti-nutritional composition, a set of 90 chickpea genotypes (66 desi and 24 kabuli) was collected from different research organizations in Pakistan. Significant variation (Tukey HSD test, p < 0.05) was perceived among genotypes for traits under investigation. The genotypes, with maximum total soluble proteins (TSPs) (34.92%), crude proteins (CPs) (30.13%), and reducing sugars (17.33 mg/g s. wt.), i.e., Punjab-2000 (desi); total free amino acids (TFAs) (3.34 g/100 g DW), i.e., Wild Hybrid-15 (desi), albumins (227.67 mg/g s. wt.), i.e., Sheenghar-2000 (desi); globulins (720 g s. wt.), i.e., ICCV-96030 (desi); salt-soluble proteins (200 mg/g s. wt.), i.e., ILWC-247 (desi); total soluble sugars (TSSs) (102.63 mg/g s. wt.), i.e., CM1051/11 (desi); non-reducing sugars (95.28 mg/g s. wt.), i.e., NIAB-CH2016 (desi); starch content (83.69%), i.e., CH55/09 (kabuli); and the genotypes with least value of anti-nutritional factors glutelin (3.33 mg/g s. wt.), i.e., Wild Hybrid-9 (desi); hordein (1.38 mg/g s. wt.), i.e., Noor-2013 (kabuli); tannins (5,425 uM/g s. wt.), i.e., Wild Hybrid-1 (desi); and phytic acid (PA) (0.18 mg/g s. wt.), i.e., Bhakhar-2011 (desi), could be the promising genotypes to formulate health-promoting plant-based food products. Data were also analyzed for principal component analysis (PCA), correlation, and agglomerative hierarchical clustering. PC-1 revealed the highest contribution (20.83%) toward cumulative variability, and maximum positive factor loading was delivered by TSSs (0.85) followed by starch content (0.729). Genotypes were grouped into three distinct clusters based on high average values of traits under investigation. Cluster I encompassed genotypes with a high mean value of CP content, albumins, hordein, and glutelin; Cluster II encompassed genotypes with a high mean value of TSPs, TSSs, non-reducing sugars, globulins, salt-soluble sugars, starch, and TFAs; Cluster III encompassed genotypes with high tannins, reducing sugars, and PA. Identified desi and kabuli genotypes exhibiting superior seed quality traits and minimal anti-nutritional factors can be used in chickpea breeding programs aimed at improving seed nutritional quality in future breeding lines.